2020
DOI: 10.1177/1049909120973200
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Provider Barriers to Patient Referral to Palliative Care

Abstract: Objective: The purpose of this study was to explore healthcare provider-perceived challenges to HBPC patient referral and elicited providers’ feedback for overcoming these challenges. Methods: We conducted a qualitative study using semi-structured interviews with 25 Medicaid managed care providers (primary care physicians, nurse practitioners, and care managers) working in the greater Los Angeles area. Our interview protocol elicited providers’ knowledge and awareness of palliative care; perceived barriers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 19 publications
(21 reference statements)
4
41
0
Order By: Relevance
“…In keeping with findings from previous research, 13 our findings showed that patients and caregivers' lack of palliative care knowledge was a barrier to HBPC use. It should be reiterated that all patients eligible for this study (and the earlier RCT) were diagnosed with cancer, COPD, or congestive heart failure, reported significant functional decline, and reported a recent emergency room or hospital admission.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In keeping with findings from previous research, 13 our findings showed that patients and caregivers' lack of palliative care knowledge was a barrier to HBPC use. It should be reiterated that all patients eligible for this study (and the earlier RCT) were diagnosed with cancer, COPD, or congestive heart failure, reported significant functional decline, and reported a recent emergency room or hospital admission.…”
Section: Discussionsupporting
confidence: 91%
“…In recent research, primary care providers also have identified this reluctance as a potential patient barrier to receiving HBPC. 13 Home healthcare agencies have cited invasion of privacy, fear of the unknown, and managing care at home as the most common reasons for refusing care at home. 27 Notably, the recruitment for the larger RCT took place prior to the start of COVID-19 as did the majority of the interviews for the current study, therefore COVID-19 most likely did not influence responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite improved outcomes with integration of the palliative care team, this remains substantially underused for many patients 113114. Barriers to palliative care referral identified by physicians include misunderstanding the role of the palliative care team,112115116 concerns that a patient may lose hope,112 and institutional culture 115. Physicians perceived patient related barriers to palliative referral as including financial, health literacy, and cultural aspects, the patient’s living situation, and disinclination for home visits 115.…”
Section: Supportive Oncologymentioning
confidence: 99%
“…Barriers to palliative care referral identified by physicians include misunderstanding the role of the palliative care team,112115116 concerns that a patient may lose hope,112 and institutional culture 115. Physicians perceived patient related barriers to palliative referral as including financial, health literacy, and cultural aspects, the patient’s living situation, and disinclination for home visits 115. Patients’ own perceived barriers to palliative care access cited in order from most to least common were preference for self-management, lack of physician recommendation, misconceptions regarding the role of palliative care, time, and cost barriers 117.…”
Section: Supportive Oncologymentioning
confidence: 99%